Influence of formulation ingredients of dry fat semi-finished products for whipping on mechanical strength of foam masses - Котляр, Олег Володимирович; Горальчук, Андрій Богданович; Гринченко, Ольга Олексіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The mechanical strength of foam-emulsion systems based on formulation ingredients of dry fat semi-finished products for whipping was studied. Experimental studies of the influence on the mechanical strength of the foam-emulsion systems of a stabilizer, surface-active substances (GMS, lecithin’s) and sunflower oil are presented. The patterns concerning the influence of concentration of kappa-carrageenan, surface-active substances, sunflower oils on the mechanical strength of foam-emulsion systems were defined in the paper for the first time. It was found that using GMS at the concentration rate of 1...6% increases the value of the boundary stress of foam offsets in foam-emulsion systems “sodium caseinate-GMS-oil” with the sodium caseinate content varying between 1.0 and 2.0% and the oil content fluctuating from 2.5 to 10.0%. Using the lecithin’s in foam-emulsion systems of “sodium caseinate-GMS-lecithin’s-oil” at the concentration ranging within 0.1...0.2% increases the mechanical strength, while at higher concentrations reduces it. It was found that for increasing the mechanical strength of foam-emulsion systems, it is appropriate to use kappa-carrageenan, which enhances the foam strength that is caused by the increase in viscosity and the formation of a gel-like structure. The rational concentration of kappa-carrageenan in the system (0.5...1.0%) was estimated, which increases the offset boundary stress by 1.5...1.6 times, i.e. amounting to 1120...1270 Pa, and the foaming capacity from 640 ± 1 % to 780...800%. The obtained results allowed developing a fundamentally new technology of dry fat semi-finished products for whipping by means of spraying a fat blend on a powder-like filler with high technological properties, which are gained at the determined concentrations of sodium caseinate, kappa-carrageenan, GMS, lecithin’s.